2021
DOI: 10.1038/s41598-021-90155-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant of TTLL11 gene and subsequent ciliary defects are associated with idiopathic scoliosis in a 5-generation UK family

Abstract: Idiopathic scoliosis (IS) is a complex 3D deformation of the spine with a strong genetic component, most commonly found in adolescent girls. Adolescent idiopathic scoliosis (AIS) affects around 3% of the general population. In a 5-generation UK family, linkage analysis identified the locus 9q31.2-q34.2 as a candidate region for AIS; however, the causative gene remained unidentified. Here, using exome sequencing we identified a rare insertion c.1569_1570insTT in the tubulin tyrosine ligase like gene, member 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 92 publications
0
15
0
Order By: Relevance
“…The POC5 gene was one of the first pieces of the puzzle of the genetic etiology of AIS, and since its identification, other genes coding for components of the primary cilia have been found to be linked to this disease [ 12 , 16 ]. Our study confirmed a higher prevalence of POC5 variants in patients with AIS compared to the general population, as Patten et al [ 13 ] already reported, and this reinforces that POC5 plays a role in the pathogenesis of AIS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The POC5 gene was one of the first pieces of the puzzle of the genetic etiology of AIS, and since its identification, other genes coding for components of the primary cilia have been found to be linked to this disease [ 12 , 16 ]. Our study confirmed a higher prevalence of POC5 variants in patients with AIS compared to the general population, as Patten et al [ 13 ] already reported, and this reinforces that POC5 plays a role in the pathogenesis of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic model for AIS remains unclear; indeed, several studies have suggested that it is a polygenic and multifactorial disease [ 9 ]. However, other analyses suggest mendelian inheritance, such as autosomal dominant or sex-related, could show with incomplete penetrance [ 10 , 11 , 12 ]. Since the advent of next-generation sequencing, candidate-gene analysis using pedigrees and population-based genome-wide association studies (GWAS) have been widely used to assess the genetic etiology of AIS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the expression of some genes related to the hedgehog (Hh) signaling is altered in kif7 mutants, suggesting a connection between the kif7 gene function and Hh pathway. Another gene, also linked to AIS susceptibility and primary cilia function, is the tubulin tyrosine ligase like gene member 11 (TTLL11) ( Mathieu et al, 2021 ). This protein induces tubulin glutamylation, required for cilia elongation.…”
Section: Emerging Roles Of Genetic Factors Related To Scoliosis Devel...mentioning
confidence: 99%
“…This protein induces tubulin glutamylation, required for cilia elongation. The function of this gene was studied in a zebrafish model, and the resulting phenotype showed spinal deformity at larvae and adult stages ( Mathieu et al, 2021 ).…”
Section: Emerging Roles Of Genetic Factors Related To Scoliosis Devel...mentioning
confidence: 99%